Synthesis of Alkyl-Substituted Tribenzopentaphenes as Versatile Polycondensed Aromatic Hydrocarbon π–π Stacking Building Blocks - Alameddine, Bassam; Caba, Sofia Martin; Schindler, Mauro; Jenny, Titus A. (Synthesis, 2012)
We show the versatile synthesis of four tribenzopentaphene derivatives bearing alkyl side chains at three different positions. Substitutions on two of these positions led to subtle intensity changes at the lines of the blue emission, whereas alkylation in the bay region led to dimerization of the pentaphene derivative, resulting in a distortion of the chromophore geometry and an emission shift to green.
Keywords: fused-ring systems; cross-coupling; Diels–Alder reaction; cyclodehydrogenation; polycycles